Analisis Pengaruh Kebijakan Spin-Off Terhadap Profitabilitas Bank Syariah di Indonesia - Netyana, Annisa Diah (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this research is to analyze the influence of the spin-off policy towards the profitability of syariah bank in Indonesia before and after spin off. The research also compares the financial performance between syariah bank that uses pure spin-off method and syariah bank that uses conversion spin-off method. The sample of this research is four sharia banks that are separated by pure spin-off method and conversion spin-off, they are BRI Syariah, Bank Bukopin Syariah, BNI Syariah and BJB Syariah. The independent variables of this research is the spin off policy, which is described by the financial performance of the syariah bank, NIM (Net Interest Margin), BOPO (Operational Revenue Operating Expense), Capital Adequacy Ratio (CAR), NPF (Net Performing Finance) and FDR (Financing Deposit Ratio), while the dependent variable used is profitability which is described by ROA ratio (Return On Asset). The method used is the panel data regression test which is continued by the average difference. The result shows that in the period before the spin-off, there are two variables and in the period after the spin-off there is only one variable that affect the ROA. There are also differences in the six variables between Islamic banks using pure spin-off method and Islamic banks using coversion spin-off method.Keywords: syariah bank, spinoff, financial performance, profitability.